PENGARUH MOTIVASI DALAM MENINGKATKAN SEMANGAT KERJA PEGAWAI PADA BAGIAN KEUANGAN DI KABUPATEN TULANG BAWANG - Naser, Abdul (Jurnal Manajemen dan Keuangan, 2012)
The problem in this study is whether motivational factors can enhance employee morale in the financial district Tulang Bawang. Purpose of the study to determine the magnitude of the effect of motivation on employee morale in the financial district Tulang Bawang. Data collection techniques used were literature study (library research) and field research (field research) that include interview, observation, documentation, and questionnaires. Used in analyzing the problems of qualitative analysis and quantitative analysis to support the. Preformance of quantitative analysis using a formula writer product moment correlation coefficient and KP (determinant coefficient). The analysis shows that the influence of motivation morale of employees in the financial district Tulang Bawang.Keywords : Motivation to Improve Morale